A forensic hypothesis for the mystery of al-Hasan's death in the 7th century: Mercury(I) chloride intoxication. (July 2016) - Burke, Nicole; Golas, Mitchell; Raafat, Cyrus L.; Mousavi, Aliyar
The puzzle of a mysterious death in the Middle Ages has been hypothesized in terms of contemporary forensic legal and scientific methods. That al-Hasan ibn-'Ali died in 669 aged just 45 has been forensically analyzed based on written sources that dictate eyewitness accounts of historical events. The report of the contemporaneous poisoning of another individual who resided under the same household as al-Hasan's and experienced similar, yet non-lethal, symptoms has served as the beginning of the analysis. In light of ancient (medieval) documents and through using mineralogical, medical, and chemical facts, it has been hypothesized that mineral calomel (mercury(I) chloride, Hg2 Cl2 ) from a certain region in the Byzantine Empire (present-day western Turkey) was the substance primarily responsible for the murder of al-Hasan.